Prioritas Kebijakan Transformasi Pelayanan RSUD Kota Cilegon 2025-2029 - Ardiyansah (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Public hospitals in industrial cities face simultaneous demands for service quality, patient safety, digital integration, financial sustainability, and preparedness for industrial emergencies. This study formulates policy priorities for the transformation of Cilegon City Regional General Hospital for 2025-2029 by translating its strategic plan into implementable policy packages. A qualitative policy analysis was conducted through document review, directed content analysis, and a priority matrix covering urgency, expected impact, implementation feasibility, and strategic alignment. The 2024 baseline shows that 74 percent of minimum service-standard indicators were achieved, 22 percent were not achieved, and 4 percent lacked data. Bed occupancy was 53.67 percent, below the ideal range, while gaps remained in specialist staffing, critical-care capacity, medical equipment, information systems, and BLUD governance. Five integrated priorities are proposed: a quality and patient-safety command system; interoperable digital data and patient-flow management; strategic workforce and teaching-hospital development; referral-capacity and industrial-resilience strengthening; and performance-based BLUD financing and collaboration. The recommendations are staged into stabilization, acceleration, and outcome consolidation so that the hospital can convert its strategic vision into measurable service improvements and accountable public value.